Identification and Analysis of Problems in the Implementation of Road Safety Audit in Lithuania - Aja Tumavičė; Igoris Kravcovas; Vilma Jasiūnienė (The Baltic Journal of Road and Bridge Engineering, 2020)
Road Safety Audits have already been tightly incorporated in the road design process throughout the world. It has proven to be an effective way of increasing road safety without requiring many resources. The cost-benefit-ratios of Road Safety Audits in developed countries are rather high. In Lithuania, the procedure on Road Safety Audits is fairly new, and the direct links between different problems and their occurrence frequency throughout the years are yet to be determined. In this paper, several audits on road safety, performed between the years 2011 and 2017 by the Road Research Institute of Vilnius Gediminas Technical University, is analysed. The trends of most relevant problem types identified in those audits throughout the years for different types of roads and streets are presented. Based on those trends, the causes of some common problems are being recognised. Recommendations on possible solutions are suggested.